Low platelet counts after induction therapy for childhood acute lymphoblastic leukemia are strongly associated with poor early response to treatment as measured by minimal residual disease and are prognostic for treatment outcome - Zeidler, Lutz; Köhler, Rolf; Bartram, Claus R. (Haematologica, the hematology journal, 2012)
Background Numerous reports have been published on the association between kinetics of leukemic cells during early treatment of childhood acute lymphoblastic leukemia and therapeutic outcome. In contrast, little is known about the prognostic relevance of normal blood counts in this setting. - Design and Methods Normal hematopoiesis during and after induction treatment (days 8, 15 and 33) was correlated with therapeutic outcome in a cohort of 256 children with acute lymphoblastic leukemia treated in one of three consecutive ALL-BFM trials at a single institute. Replication analysis of positive findings was performed in an independent cohort of 475 patients from the ALL-BFM 2000 multicenter trial. - Results A platelet count in the first quartile on treatment day 33 and a neutrophil count above the median on day 8 were significantly associated with treatment outcome, conferring multivariate risk ratios for an event of 3.27 (95% confidence interval 1.60-6.69) and 2.26 (95% confidence interval 1.23-4.29), respectively. Replication analysis confirmed the prognostic effect of platelet count on treatment day 33 and demonstrated a strong association with minimal residual disease-based risk group distribution (P<0.00001). - Conclusions Platelet counts after induction treatment may improve treatment stratification for patients with childhood acute lymphoblastic leukemia and be of particular interest in non-minimal residual disease-based trials. (ALL-BFM 2000 is registered at: ClinicalTrials.gov: NCT00430118. National Cancer Institute: Protocol ID 68529)